Adipokines enhance oleic acid-induced proliferation of vascular smooth muscle cells by inducing CD36 expression. (July 2015) - Schlich, Raphaela; Lamers, Daniela; Eckel, Jürgen; Sell, Henrike
Abstract Adipose tissue is not only releasing lipids but also various adipokines that are both dysregulated in the obese state and may contribute to obesity-associated vascular dysfunction and cardiovascular risk. We have previously shown that the combination of adipocyte-conditioned medium (CM) and oleic acid (OA) increases proliferation of human vascular smooth muscle cells (VSMC) in a synergistic way. We identified vascular endothelial growth factor (VEGF) as a component within CM that is responsible for most of the observed effects. In this study, we investigate novel mechanisms that underlie the combined effects of adipokine and oleic acid-induced proliferation of VSMC. Oleic acid leads to significant lipid accumulation in VSMC that is further enhanced by the combined treatment with CM. Accordingly CM stimulates CD36 expression in VSMC while OA is not affecting CD36. Silencing of CD36 was established and prevents lipid accumulation in all tested conditions. CD36 silencing also abrogates CM- and OA-induced proliferation and considerably reduces proliferation induced by the combination of CM and OA. At the same time, VEGF secretion and VEGF-receptor 1 (VEGF-R1) by VSMC was not affected by CD36 silencing. However, VEGF was not able to induce any proliferation in VSMC after CD36 silencing that also blunted VEGF-induced extracellular signal-regulated kinase (ERK) activation. Finally, combined silencing of CD36 together with a blocking antibody against VEGF prevented most of CMOA-induced proliferation. In conclusion, our results demonstrate that CD36 is mediating CM-induced proliferation of VSMC. Induction of CD36 by adipokines enhances the response of VSMC towards VEGF and OA.